Four opportunities for studies of ecological succession - Prach, Karel; Walker, Lawrence R (Trends in ecology & evolution, 2011)
Lessons learned from the study of ecological succession have much to offer contemporary environmental problem solving but these lessons are being underutilized. As anthropogenic disturbances increase, succession is more relevant than ever. In this review, we suggest that succession is particularly suitable to address concerns about biodiversity loss, climate change, invasive species, and ecological restoration. By incorporating modern experimental techniques and linking results across environmental gradients with meta-analyses, studies of succession can substantially improve our understanding of other ecological phenomena. Succession can help predict changes in biodiversity and ecosystem services impacted by invasive species and climate change and guide manipulative responses to these disruptions by informing restoration efforts. Succession is still a critical, integrative concept that is central to ecology.
Keywords: Biodiversity; Biota; Meta-Analysis as Topic; biodiverzita; podnebí; zachování přírodních zdrojů; zavlečené druhy; metaanalýza jako téma; Conservation of Natural Resources; Ecology; Climate; společenstvo; ekologie; Introduced Species